FORMULATION AND EVALUATION OF SIMVASTATIN GASTRORETENTIVE DRUG DELIVERY SYSTEM - N., Manjunath P.; S., Satish C.; S., Vasanti; C., Preetham A.; Ras, Naidu (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of this study was to formulate and evaluate gastro retentive drug delivery system (GRRDS) using an effervescent approach for simvastatin. Methods: Floating tablets were prepared using directly compressible polymers hydroxypropyl methylcellulose (HPMC) K100M, HPMC K4M and carboxymethylcellulose sodium (NaCMC). The prepared tablets were subjected to pre-formulation studies like Compressibility index, Hausner ratio and post compression parameters like buoyancy/floating test and In vitro dissolution study. Results: Drug-excipient compatibility studies performed with the help of FTIR instrument indicated that there were no interactions. The DSC thermogram of the formulations revealed that crystalline form of simvastatin existed in the formulation which was confirmed by X-ray powder diffraction. Dissolution studies indicated that there was a decrease in the drug release with an increase in the polymer viscosity. The tablets prepared with low-viscosity grade HPMC K4M exhibited short Buoyancy Lag Time and floated for a longer duration as compared with formulations containing high viscosity grade HPMC K100M. The ‘n' value for dissolution studies for all the formulations was found to be in the range of 0.647 to 0.975 indicating non-Fickian or anomalous drug transport. Conclusion: The drug release rate and floating duration of tablets depended on the nature of the polymer and other added excipients. The release rate of the drug can be optimized by using different ratios of polymers and other excipients. The formulation F8 achieved the optimized batch and complied with all the properties of the tablets.